The Impact of Strategic Orientation on Governance Principles Implementation in Banks Operating in Yemen - د. بشير محمد الحمادي (مجلة الدراسات الاجتماعية, 2023)
The study aimed to know the impact of five-dimensional strategic orientation, namely (vision, mission, values, goals, and strategic objectives) on implementing governance principles of (18) banks, which constitute all the banks in Yemen. The analytic descriptive method was followed and the whole survey sampling method was utilized. The respondents were (417) of the administrative leaders concerned with implementing the governance principles of bank. A number of conclusions were reached, notably that strategic orientation has a positive impact on the implementation of bank governance principles; the level of which varies according to the three dimensions (mission, vision and strategic objectives) with a greater impact than those of (values and goals). In addition, the implementation of the principles of governance of Yemeni banks is essential to contribute to the market success and growth for the development of Yemeni economy, and to achieve success in the financial and administrative performance in the banking business in the financial and administrative performance. In the light of the results, it is recommended to increase banks' interest in strategic orientation in all its dimensions, as it has a positive impact on the implementation of governance principles. Besides, the study recommends benefiting from experience exchange, knowledge transferential acquisition among senior, middle and supervisory management in the strategic field as well as implementing the governance principles in banks.